An introspective view of sustainable Cohousing with the Malaysian housing concept - Jumadi, N. (EDP Sciences, 2016)
Sustainable development strategies are becoming demanded in assisting in wealth distribution and improving living conditions for mankind. A sustained community is one of the sustainable development agendas that encourage community involvement and participation in contributing to sustainability. Moreover, with the rapid population growth, especially in urban cities as the proportion of urban dwellers will reach two-thirds of the world population, this will lead to several problems including the social life changing intensely. Sustainable Cohousing is one of the suggested answers for an innovative form of neighbourly accommodation. Generally, Cohousing is formed by a group of people who are committed to living as a community and who actively participate in the design and operation to shape their own neighbourhood. Through this concept, the community can decide how they can implement sustainability principles in terms of social, economical and environmental terms in their neighbourhood. Therefore, it is important to bring back the sense of togetherness amongst the people and improve their social wellbeing through an effective neighbourhood. The objective of this study is to isolate the basic concept of Cohousing and to identify the conceptual framework of Sustainable Cohousing that may apply to improving the sustainable living in Malaysia. The research methodology was through identifying and reviewing the issues in existing literature on cohousing chosen from various dimensions, such as principles and elements, sustainable value, development model and so on, which can be suited with the Malaysian culture. The findings of this research are useful for property development practitioners and policy makers in promoting sustainability through the new concept of modern housing.